2013
DOI: 10.1063/1.4819251
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulation of shock formation for super-Alfvénic expansion of laser ablated debris through an ambient, magnetized plasma

Abstract: Two-dimensional hybrid simulations of perpendicular collisionless shocks are modeled after potential laboratory conditions that are attainable in the LArge Plasma Device (LAPD) at the University of California, Los Angeles Basic Plasma Science Facility. The kJ class 1053 nm Nd:Glass Raptor laser will be used to ablate carbon targets in the LAPD with on-target energies of 100-500 J. The ablated debris ions will expand into ambient, partially ionized hydrogen or helium. A parameter study is performed via hybrid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…One of its most significant findings was the unanticipated displacement of the barium ion 'comet head' (and an oppositely directed deflection of the streaming hydrogen ions) transverse to both the solar wind flow and the interplanetary magnetic field, defying the conventional expectation that the barium ions would simply move downwind 4 . While subsequent theoretical and computational e orts [5][6][7] to understand the cause of the transverse motion reached di ering conclusions, several authors 5 attributed the observations to Larmor coupling 8,9 , a collisionless momentum exchange mechanism believed to occur in various astrophysical and space-plasma environments 10,11 and to participate in cosmic magnetized collisionless shock formation [12][13][14] . Here we present the detection of Larmor coupling in a reproducible laboratory experiment that combines an explosive laser-produced plasma cloud with preformed, magnetized ambient plasma in a parameter regime relevant to the AMPTE barium releases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of its most significant findings was the unanticipated displacement of the barium ion 'comet head' (and an oppositely directed deflection of the streaming hydrogen ions) transverse to both the solar wind flow and the interplanetary magnetic field, defying the conventional expectation that the barium ions would simply move downwind 4 . While subsequent theoretical and computational e orts [5][6][7] to understand the cause of the transverse motion reached di ering conclusions, several authors 5 attributed the observations to Larmor coupling 8,9 , a collisionless momentum exchange mechanism believed to occur in various astrophysical and space-plasma environments 10,11 and to participate in cosmic magnetized collisionless shock formation [12][13][14] . Here we present the detection of Larmor coupling in a reproducible laboratory experiment that combines an explosive laser-produced plasma cloud with preformed, magnetized ambient plasma in a parameter regime relevant to the AMPTE barium releases.…”
mentioning
confidence: 99%
“…This interaction, termed Larmor coupling, thus allows the moving debris cloud to pick up the swept-over ambient ions. Larmor coupling has received extensive theoretical and numerical investigation over the past few decades, both as a basic plasma process 8,9 and as a key mechanism in the evolution of various astrophysical and space phenomena, including man-made ionospheric explosions 11 , the AMPTE artificial comets 5 , and the formation of cosmic magnetized collisionless shocks [12][13][14] . However, this process has never before been observed in a laboratory setting.…”
mentioning
confidence: 99%
“…Since it can also be shown 24 that debris ions traveling too fast will slip through the ambient plasma without coupling, it is necessary to have a further constraint on the debris ions. We have shown previously in simulations 25 that for a debris plasma dominated by a single ion species (see Sec. IV A for further discussion), the condition R M =q d > 0:7, where q d is the debris ion gyroradius, must be satisfied for a shock to form.…”
Section: Theory and Simulationsmentioning
confidence: 91%
“…Recentry, Niemann et al have reported the first observation [45,46] of collisionless MHD perpendicular shock, which was predicted by hybrid-simulation [47], using the Large Plasma Device [48] and a high-energy laser system [49]. No clear particle acceleration has been investigated experimentally for the MHD shock yet.…”
Section: Introductionmentioning
confidence: 99%